The Social Impacts of the February 6, 2023, Kahramanmaraş-Centered Earthquakes on Entrepreneurs in Turkey - Marangoz, Mehmet; GÖRGÜLÜ, Hatice Hicret; İZCİ, Çağrı (International Journal of Contemporary Economics and Administrative Sciences, 2025)
The aim of this study is to analyze the social impacts of the February 6, 2023, Kahramanmaraş-centered earthquakes on entrepreneurs and to identify the necessary strategies for their reconstruction. To explore the social impacts of the earthquakes on entrepreneurs in the region, a semi-structured interview method, a qualitative data collection tool, was employed. Due to limitations in time and resources, the research was conducted in five provinces that were both severely affected by the earthquakes and economically significant to the region: Kahramanmaraş, Adıyaman, Malatya, Gaziantep, and Hatay. In-depth interviews were carried out with presidents and representatives of the Chambers of Commerce and Industry, Chambers of Commerce, Chambers of Industry, and Commodity Exchanges across these five provinces. In total, 11 officials from various institutions were interviewed, with the interviews averaging 48 minutes in duration. The qualitative analyses identified several dimensions of the social impacts of the earthquakes, including social relations, social life, health, education, housing (households), work patterns, disaster management processes, social support, migration, social structure, and collaboration. The findings highlighted disaster management processes and disruptions to social life as the most critical issues. Addressing these challenges and enabling entrepreneurs to recover to pre-disaster conditions necessitate concerted efforts and responsibilities, particularly from public institutions, non-governmental organizations (NGOs), and the entrepreneurs themselves.